High‐temperature 2D Fermi surface of SrTiO3 studied by energy‐filtered PEEM. (3rd September 2018) - Mathieu, Claire; Gonzalez, Sara; Lubin, Christophe; Copie, Olivier; Feyer, Vitaliy; Schneider, Claus M.; Barrett, Nick
Abstract : Functional oxides displaying phenomena such as 2D electron gas (2DEG) at oxide interfaces represent potential technological breakthroughs for post‐CMOS (Complementary Metal Oxide Semiconductor) electronics. Noninvasive techniques are required to study the surface chemistry and electronic structure underlying their often unique electrical properties. The sensitivity of photoemission electron microscopy (PEEM) to local potential, chemistry, and electronic structure makes it an invaluable tool for probing the near surface region of microscopic regions and domains of functional materials. In particular, PEEM allows single shot acquisition of the 2D Fermi surface and full angular probing of the symmetry‐induced intensity modulations. We present results demonstrating a 2DEG at the surface of SrTiO3 (001) at 140 K. The 2DEG is created by soft X‐ray irradiation and can be reversibly controlled by a combination of soft X‐rays and oxygen partial pressure.